DEVELOPMENT AND VALIDATION OF PHANTOM FOR ULTRASONOGRAPHIC SIMULATOR FOR PULMONARY TISSUES - Alfa Nabila, Citra
Ultrasonography (USG) is one of the medical diagnostic methods that utilizes high- frequency acoustic waves. Ultrasound can be used as an alternative method of examining the condition of the lungs, although it has some challenges such as air- containing lung tissue, significant impedance differences between thoracic muscle tissue and pulmonary tissue as well as ribbons that can absorb almost the entire ultrasonic wave delivered by the ultrasound probe. In order to produce accurate diagnosis in the lung ultrasound, the accuracy of the operator's analysis is required in the testing. Before testing, the operator is required to understand basic knowledge of ultrasounds, have technical capabilities to operate the targeting ultrasound device, and know the features of the ultrasonic imaging produced in specific lung conditions. Operators also need to observe some abnormal conditions of the lungs in order to have a pulmonary ultrasound. In the learning process of medical personnel, the need for lung phantom for ultrasound becomes quite significant.